Comparison of stented versus non-stented patients of ureteric calculi after intracorporeal lithotripsy - Khan, Azhar A.; Khan, Suhail M.; Kanth, Anzeen N.; Khan, Aymen M.; Wani, Owais Ahmad (International Surgery Journal, 2022)
Background: A ureteric stent is a tube that is inserted into the ureter to treat and prevent urinary blockage. Stenting is most commonly used to treat stone disease in the ureter during definitive procedures such as ureteroscopy and extracorporeal shock wave lithotripsy. The stent that remains in place frequently causes urinary tract infection and discomfort in the suprapubic area. We report results of our study which attempted to assess stent-related complaints following semirigid ureteroscopy and intracorporeal lithotripsy. Methods: A total of 70 individuals were randomised to stented(n=35) and non-stented group (n=35) between September 2017 and March 2020. Under spinal anaesthesia URSL was performed. Patients' success, operation time, postoperative pain score, analgesic demand, stent-related symptoms, and risk of ureteral stricture development were all evaluated. Results: There was no statistically significant difference between the two treatment groups in terms of ureteral dilation, intracorporeal lithotripsy, or the incidence of intraoperative and postoperative problems. It was found that non-stented group was cost effective as compared to stented group, Furthermore, removal of the stent using local anaesthesia was more painful than the initial ureteroscopy procedure using regional (spinal) anaesthesia. Postoperative pain in non-stented group (n=6) was less than stented group (n=17). Conclusions: Routine placement of ureteral stent is not necessary in uncomplicated cases of ureteric calculi following ureteroscopy, the decision being made on the basis of intra operative findings, where the risks clearly outweigh the benefits offered by stenting.